Finite Element Analysis of the Structural Behavior of a Corroded Pipe Culvert - Qiang Ma; Chuchen Xi; Jianyu Li; Xuesong Lu (Applied Sciences)
The stress analysis of buried pipe culverts is a complex task, and accurately characterizing the deterioration of mechanical properties caused by corrosion poses significant challenges. In this study, the finite element analysis software PLAXIS 3D was employed to construct a numerical simulation model of a pipe culvert. By varying the stiffness and thickness of either the entire structure or specific sections, different degrees of corrosion were simulated to investigate the influence of various cross-sectional shapes on corrosion effects. Multiple experimental controls were set to analyze both the bearing capacity and deformation characteristics under different conditions. The findings reveal that different levels of corrosion have distinct impacts on the deformation behavior of pipe culverts. Overall corrosion has the most significant effect on the overall deformation, while crown and middle corrosion show a similar effect on stiffness-related deformations. In contrast, invert corrosion has minimal impact on the stiffness-related deformation. Corrosion affects circular and elliptical pipe culverts similarly. However, the circular pipe culvert is evidently influenced by overall corrosion more significantly than the elliptical ones due to the combined effects from overall and local corrosion in their deformations. Through finite element numerical simulation, it can be used as a reference for practical engineering design and construction.